Ответ:
y = (x-2)^2 - 9.
Находим корни данного уравнения:
y = 0 => (x-2)^2 - 9 = 0 => (x-2)^2 = 9 => x-2 = 3 или x-2 = -3 => x = 5, x = -1
S = "интеграл" от -1 до 5 ( (x-2)^2 - 9)dx = 1/3 * (x-2)^3 - 9x от -1 до 5 = -9 + 9 - 9 + 45 = 36
Ответ: 36
Пошаговое объяснение:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
y = (x-2)^2 - 9.
Находим корни данного уравнения:
y = 0 => (x-2)^2 - 9 = 0 => (x-2)^2 = 9 => x-2 = 3 или x-2 = -3 => x = 5, x = -1
S = "интеграл" от -1 до 5 ( (x-2)^2 - 9)dx = 1/3 * (x-2)^3 - 9x от -1 до 5 = -9 + 9 - 9 + 45 = 36
Ответ: 36
Пошаговое объяснение: